First person - Mugagga Kalyesubula and Ramgopal Mopuri (The Company of Biologists, 2021)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Mugagga Kalyesubula and Ramgopal Mopuri are co-first authors on 'High-dose vitamin B1 therapy prevents the development of experimental fatty liver driven by overnutrition', published in DMM. Mugagga is a PhD student in the lab of Dr Hay Dvir at the Volcani Center - Agricultural Research Organization (ARO), Rishon LeZion, Israel and The Hebrew University of Jerusalem, Rehovot, Israel, investigating therapy development for chronic metabolic diseases such as non-alcoholic fatty liver disease. Ramgopal is a postdoctoral researcher in the lab of Dr Hay Dvir at the Volcani Center - ARO in Rishon LeZion, Israel, developing therapeutic approaches for the management of fatty liver diseases.